Global Christians in Edinburgh - Chow, Alexander; Wild-Wood, Emma; Hatzaw, Nuam (Centre for the Study of World Christianity, 2023)
The ‘Global Christians in Edinburgh’ project highlights the global diversity of Christianity in Edinburgh and the collaborative efforts of these communities. It coincides with a historic period of both downturn in many historic Edinburgh churches and upsurge in Christianity amongst migrants coming from Africa, Asia, Latin American, Oceania, and other parts of Europe, resulting in the creation of new fellowships, (sub)congregations, and worship services/mass.
Keywords: World Christianity; migration; diaspora; Edinburgh; Scotland